The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1101/828152
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The thrombopoietin receptor agonist eltrombopag inhibits human cytomegalovirus replication via iron chelation

Abstract: m.michaelis@kent.ac.uk (MM) 18 19 Acknowledgements 20 The work was supported by the Hilfe für krebskranke Kinder Frankfurt e.V. and the 21 Frankfurter Stiftung für krebskranke Kinder. 22 23 2 Abstract 24 The thrombopoietin receptor agonist eltrombopag was successfully used 25 against human cytomegalovirus (HCMV)-associated thrombocytopenia refractory to 26 immunomodulatory and antiviral drugs. These effects were ascribed to effects of 27 eltrombopag on megakaryocytes. Here, we tested whether eltrombopag may al… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…They confirmed that EPAG is a powerful iron chelator, and when it was used with deferasirox, the iron chelation capacity increased in thalassemia patients [21]. In another study, EPAG therapy was shown to inhibit replication of human cytomegalovirus infection by iron chelation [22]. Following these findings, a clinical study with a limited number of children with Ch-ITP revealed that EPAG treatment reduced the patients' MCV and ferritin levels, ultimately causing IDA [23].…”
Section: Discussionmentioning
confidence: 86%
“…They confirmed that EPAG is a powerful iron chelator, and when it was used with deferasirox, the iron chelation capacity increased in thalassemia patients [21]. In another study, EPAG therapy was shown to inhibit replication of human cytomegalovirus infection by iron chelation [22]. Following these findings, a clinical study with a limited number of children with Ch-ITP revealed that EPAG treatment reduced the patients' MCV and ferritin levels, ultimately causing IDA [23].…”
Section: Discussionmentioning
confidence: 86%
“…It inhibited CMV replication in vitro via iron chelation, and synergistically increased the anti-CMV activity of ganciclovir. 35 Our study has some limitations in addition to its retrospective nature. First, in most of the cases the CMV workup took place after the failure of steroid treatment.…”
Section: Discussionmentioning
confidence: 92%
“… 4 In more recent studies, however, functionally relevant iron-chelating effects were reported in cardiomyocyte cell lines, 5 osteoclasts, 6 neonatal hippocampal neurons, 7 and human cytomegalovirus. 19 Depending on the specific cell type and clinical situation, the iron-chelating effects of ELT could be either clinically beneficial (as for cardiomyocytes in clinical conditions associated with iron overload) or detrimental (such as for neonatal neurons).…”
Section: Discussionmentioning
confidence: 99%